1990
DOI: 10.1063/1.345224
|View full text |Cite
|
Sign up to set email alerts
|

Induced emission cross section of Nd:Y3Al5O12 ceramics

Abstract: Optical absorption and emission spectra have been measured for Nd-doped Y3Al5O12 ceramics obtained by a urea precipitation method. The optical properties of the ceramics are almost the same as those of single crystals grown by the Czochralski method and floating-zone method, except for a higher background absorption of 2.5–3 cm−1. The energy-level structure for Nd3+ in the Y3Al5O12 ceramics is determined for a 1-at. % Nd concentration. The induced emission cross section for the 1-at. %-Nd-doped ceramic is calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(43 citation statements)
references
References 22 publications
2
41
0
Order By: Relevance
“…In polycrystalline form, there is theoretically no size limitation. Undoped YAG translucent ceramics have been produced by de With et al, 8 and Nd-doped polycrystalline YAG by Sekita et al 9 Major work on the subject has been provided by teams of Ikesue and Konoshima Chemicals. 10 Recently, Rabinovitch et al 7 have demonstrated that high transparency and laser efficient polycrystalline YAG:Nd can be synthesized by sintering of commercial oxides.…”
Section: Introductionmentioning
confidence: 98%
“…In polycrystalline form, there is theoretically no size limitation. Undoped YAG translucent ceramics have been produced by de With et al, 8 and Nd-doped polycrystalline YAG by Sekita et al 9 Major work on the subject has been provided by teams of Ikesue and Konoshima Chemicals. 10 Recently, Rabinovitch et al 7 have demonstrated that high transparency and laser efficient polycrystalline YAG:Nd can be synthesized by sintering of commercial oxides.…”
Section: Introductionmentioning
confidence: 98%
“…The fabrication of transparent ceramics of laser quality is a very delicate process. Various attempts to obtain laser quality transparent ceramics of these materials were reported [6,7] but only recently high quality transparent ceramics of cubic laser complex oxide materials, such as garnets (YAG) or sesquioxides (Y 2 O 3 , Sc 2 O 3 ) doped with laser ions such as Nd 3+ or Yb 3+ , in concentrations much larger than possible for the melt grown-crystals, have been produced and successful laser operation was obtained. The ceramics become transparent when the size of the scattering centres, that are dominantly the pores between the crystalline grains, is very small, of the order of micrometer, and their volume density is low, in the range of ppm or tens of ppm.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to synthesize polycrystalline translucent YAG ceramics for laser application have been reported in. [1][2][3] Another application of rare-earth doped YAG in the powder form as phosphor for displays, due to its good stability to high intensity electron irradiation, should be mentioned. 4 High temperature creep resistance is an attractive YAG property.…”
Section: Introductionmentioning
confidence: 99%